Kinetic analysis of peroxide cured natural rubber/layered silicate nanocomposites using thermogravimetry - Rajan R; Fancy M.A; George K.E; Madhusoodanan K.N; Varghese S (Rubber Science, 2018)
The thermal stability and kinetics of thermal degradation of natural rubber/layered silicate nanocomposites were studied by thermogravimetric analysis (TGA). The nanoclays selected were cloisite Na+, cloisite 10A, cloisite 15A and cloisite 93A. Gum and commercial clay (English Indian clay) were used as reference materials. Dicumyl peroxide (40;active) was used as the crosslinking agent. The activation energy for the degradation of NR/layered silicate nanocomposites was determined by applying Liu and Fan method. Results showed that the thermal degradation is a first order reaction and organically modified clays exhibited the highest thermal stability.
Keywords: Activation energy; Kinetic analysis; Liu abd Fan method; Thermal degradation; Thermogravimetric analysis